The Simultaneous Acute Release of Tissue-Type Plasminogen Activator and von Willebrand Factor in the Perfused Rat Hindleg Region - Tranquille, N; Emeis, J J (Thrombosis and Haemostasis, 1990)
In perfused rat hindlegs, platelet-activating factor and bradyki-nin induced the acute release of both tissue-type plasminogen activator (t-PA) and von Willebrand Factor (vWF). The time course of release was similar for both proteins, and the amounts of t-PA and vWF released under various conditions were closely correlated. Release of both t-PA and vWF required extracellular calcium, and could be induced by the calcium ionophore A-23187. Protein synthesis was not required for release to occur.Phorbol myristate acetate also induced release of t-PA and vWF, though with a different time course; DDAVP was inactive.The results suggest that the release of t-PA, and that of vWF, are closely linked at the cellular level.